Studi Laboratorium Pengaruh Variasi Temperatur Pemanasan Arang Batok Kelapa Terhadap Thickening Time dan Free Water Semen Pemboran - Novrianti, Novrianti; Umar, Mursyidah (Journal of Earth Energy Engineering, 2017)
The cementing process can determine successful oil well when producing oil to the surface. Planning the time required for the cement suspension to achieve consistency of 100 UC (unit of consistency) or thickening time and the maximum limit of water content used is the nature of cement slurry that affect the quality of cement. The addition of coconut shell charcoal with variation of heating temperature 400 0C, 500 0C, 600 0C, 700 0C, 800 0C, 900 0C to the basic cement was done in this study to determine the effect of heating temperature of coconut shell charcoal to thickening time and free water cement drilling. This experimental study uses an additive material derived from coconut shell charcoal. This experiment begins by preparing a cement sample with a coconut shell charcoal concentration of 1%. The coconut shell charcoal used has different heating temperatures of 400 0C, 500 0C, 600 0C, 700 0C, 800 0C, 900 0C. Suspense cement is made by mixing G grade cement, water, bentonite, CaCl2 and coconut shell charcoal. Thickening time test using atmospheric equipment consistometer and measuring cups used to determine the value of free water. The results showed that the thickening time and free water values ââwere influenced by the heating temperature of coconut shell charcoal. The higher coconut shell charcoal temperature used in the cement suspension make thickening time of the cement suspension becomes shorter. The optimum heating temperature of coconut shell charcoal is 700 0C with thickening time of 1 hour 38 seconds 52 seconds and free water 1.2 mL.